Pensamientos irracionales y su repercusión en la salud mental en una paciente de 64 años con enfermedad catastrófica del cantón Quinsaloma - Puente Zapata, Delia Madeleyne (2023)
The objective of this case study is to determine the impact of irrational thoughts on mental health in a 64-year-old patient with catastrophic disease of Quinsaloma Canton, to which three specific objectives are added, as first identifying the types of irrational thoughts presented by the patient, also assessing the state of the mental health of the patient and finally analyzing the relationship that exists between the irrational thoughts and the mental health of the patient. This research has the methodology of a correlational type, not experimental and is mixed approach. To evaluate the investigatory variables and the psychological state of the patient, techniques such as Interview, clinical observation, clinical history and psychometric tests were used, such as the TCI Questionnaire of Irrational Beliefs (TCI) and the L. Derogatis SCL-90-R Inventory of Symptoms. The diagnosis of the metal state of the patient was established with the help of the applied reagents, the theoretical bases, methodology and criteria of the DSM-V and CIE-10. Once the results were collected, the intervention was performed using rational emotional behavioral therapy techniques, which were carried out over five sessions, finally it could be concluded that if irrational thoughts affect the mental health of the patient.